2015
DOI: 10.1149/2.0471506jes
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cuprous Ion in Copper Electrodeposition Acceleration

Abstract: We have previously reported that the cuprous ion concentration inside the via increases during the reverse portion of a periodic reverse pulse waveform. The void decreases and bottom-up via filling is achieved by increasing this reverse current during copper electrodeposition. Acceleration occurs at the via bottom by increasing the reverse current for cathodic polarization. J. R. White's work showed a low cuprous ion concentration during cathodic polarization without additives. During cathodic polarization, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
37
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 20 publications
1
37
1
Order By: Relevance
“…As a result, the copper deposition rate at the via bottom becomes greater than that in other areas of the via, which leads to bottom-up copper deposition and copper bump formation. Kondo et al [14][15] demonstrated that cupric ions react with sodium 3-mercapto-1-propanesulfonate (MPS) or bis-(3-sulfopropyl)-disulfide (SPS) to form Cu(I)-thiolate. The Cu(I)-thiolates accumulate in the microvia to locally accelerate the copper electrodeposition and achieve bottomup filling.…”
mentioning
confidence: 99%
“…As a result, the copper deposition rate at the via bottom becomes greater than that in other areas of the via, which leads to bottom-up copper deposition and copper bump formation. Kondo et al [14][15] demonstrated that cupric ions react with sodium 3-mercapto-1-propanesulfonate (MPS) or bis-(3-sulfopropyl)-disulfide (SPS) to form Cu(I)-thiolate. The Cu(I)-thiolates accumulate in the microvia to locally accelerate the copper electrodeposition and achieve bottomup filling.…”
mentioning
confidence: 99%
“…Cuprous ion plays an important role in copper electrodeposition acceleration. 33 During the copper deposition process, the sulfone group of the MPS responds the cupric ion and produces the Cu(I)-thiolate complex. 33,34 This Cu(I)-thiolate complex floats in the via and releases the cuprous ion through oxidization reaction.…”
Section: Resultsmentioning
confidence: 99%
“…33 During the copper deposition process, the sulfone group of the MPS responds the cupric ion and produces the Cu(I)-thiolate complex. 33,34 This Cu(I)-thiolate complex floats in the via and releases the cuprous ion through oxidization reaction. The released cuprous ion is rapidly deposited as metallic copper on the electrode and the copper electrodeposition is accelerated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the merits of high throughput, low process cost, and good film quality, Cu electroplating has a wide application, from traditional Cu foil production to state-of-the-art semiconductor metallization processes. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] The Cu plating solution typically contains small amounts of organic additives, 1-16 which enhance the uniformity, 13 brightness, 14 and mechanical properties of the Cu film. 15 In addition, for particular application to damascene Cu plating, the additives enable bottom-up filling at trenches or vias by controlling the relative deposition rates of Cu at the top and bottom of the features.…”
mentioning
confidence: 99%